1995
DOI: 10.1093/ajcp/103.4.466
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Responses to Biomaterials

Abstract: Implanted biomedical devices are of increasing importance in modern medical care. However, surprisingly little is known of the factors that determine biocompatibility of the materials used in these devices. These materials, although generally inert and non-toxic, can mediate a variety of adverse reactions, including inflammation, fibrosis, coagulation, and infection. This brief review focuses on the inflammatory responses (including fibrosis) that commonly occur around implanted biomaterials. Host proteins tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
304
1
8

Year Published

1998
1998
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 441 publications
(318 citation statements)
references
References 77 publications
5
304
1
8
Order By: Relevance
“…11,13,19,20,[56][57][58] The collagenous capsule acts as a barrier to the diffusion of drugs and also blocks the supply of nutrients to the encapsulated cells in cell delivery systems. 11,[18][19][20]59 By diminishing biomaterial-mediated fibrotic reactions and accompanied collagenous diffusion barrier formation, the drug release properties, life-span and sensor sensitivity could be significantly enhanced.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,13,19,20,[56][57][58] The collagenous capsule acts as a barrier to the diffusion of drugs and also blocks the supply of nutrients to the encapsulated cells in cell delivery systems. 11,[18][19][20]59 By diminishing biomaterial-mediated fibrotic reactions and accompanied collagenous diffusion barrier formation, the drug release properties, life-span and sensor sensitivity could be significantly enhanced.…”
Section: Discussionmentioning
confidence: 99%
“…9 However, many of these medical devices fail to produce long term therapeutic effect raising serious concerns over the efficiency of these implants. [10][11][12][13][14][15][16][17] For example, the chemotherapeutic doxorubicin delivering millirods has been reported to lose efficacy 8 days post subcutaneous implantation. 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, no systemic effects on any of the studied blood parameters, including CD4 cell count and viral load, were observed in this study. PLA has advantages over other facial implants in that it is hypoallergenic and biodegradeable, unlike silicon particles, which remain permanently resident in the skin and may trigger inflammatory reactions [10]. Additionally, the administration technique enables individualization to suit the patient's facial contours and leads to development of increased skin thickness but with retention of normal skin appearance and texture.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the role of protein conformation in modulating receptor recognition and cellular function, inconsistencies in the literature exist between the type and amount of adsorbed proteins and the subsequent cellular behavior [4,5]. For example, monocyte adhesion on a poorly adhesive surface is enhanced by adsorbed IgG [6], while others have shown that fibrinogen is more critical for phagocyte adhesion on biomaterials [7]. Others and we have demonstrated that macrophage adhesion is mainly modulated by the substrate and the extracellular matrix protein such as fibronectin [8,9].…”
Section: Introductionmentioning
confidence: 99%